2015
DOI: 10.1111/sjop.12257
|View full text |Cite
|
Sign up to set email alerts
|

Stability and predictors of psychopathic traits from mid‐adolescence through early adulthood

Abstract: High levels of psychopathic traits in youth are associated with multiple negative outcomes including substance misuse, aggressive behavior, and criminality. Evidence regarding stability of psychopathic traits is contradictory. No previous study has examined long-term stability of psychopathic traits assessed with validated clinical measures. The present study examined the stability of psychopathic traits from mid-adolescence to early adulthood and explored adolescent factors that predicted psychopathic traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…A second limitation of the present study was that psychopathy among some participants was assessed 2 years prior to the scan. However, evidence shows stability of scores from mid-adolescence to adulthood ( McMahon et al , 2010 ; Hemphälä and Hodgins, 2014 ; Hemphälä et al , 2015 ). At the imaging resolution used in the present study, abnormalities of the fornix and stria terminalis may not have been distinguishable.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second limitation of the present study was that psychopathy among some participants was assessed 2 years prior to the scan. However, evidence shows stability of scores from mid-adolescence to adulthood ( McMahon et al , 2010 ; Hemphälä and Hodgins, 2014 ; Hemphälä et al , 2015 ). At the imaging resolution used in the present study, abnormalities of the fornix and stria terminalis may not have been distinguishable.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Psychopathy comprises four facets of personality and behavior: an interpersonal facet indexing conning, manipulation, and deceitfulness; an affective facet indexing callousness, lack of empathy and guilt, and failure to take responsibility for one’s own actions; a life-style facet indexing risk-taking, rebelliousness, and impulsivity; and one facet indexing antisocial behavior ( Hare, 2003 ). These facets vary dimensionally in the population ( Guay et al , 2007 ), remain relatively stable from childhood through early adulthood and predict multiple adverse psychosocial and mental health outcomes, and criminal offending, over and above conduct problems ( McMahon et al , 2010 ; Hemphälä and Hodgins, 2014 ; Hemphälä et al , 2015 ; Waller et al , 2016 ). High scores on all four facets of the Psychopathy Checklist Revised (PCL-R) ( Hare, 2003 ) identify the syndrome of psychopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The display of psychopathic behaviors is a reliable predictor for poor academic achievement, criminality, behavioral problems, and for adverse psychosocial consequences and mental health (8,9). The prevalence of psychopathy is approximately 1% in the general population (10,11), 3% in forensic population (12), 4% amongst corporate managers (13), and 20% in prison population (14).…”
Section: Introductionmentioning
confidence: 99%
“…By Table 3 Linear regression models of different type of recent (in the last 12 months) victimization predicting APSD-SR total scores in the total sample (n = 4855). assessing a sample of adolescents from juvenile substance misuse clinic, Hemphala et al (2015) reported that childhood physical abuse was not associated with PCL-R scores in youth. Our study contributes to the present literature by showing that severe forms of victimization experiences (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, severely abused juvenile offenders score high on psychopathy measures (Campbell et al, 2004;Krischer & Sevecke, 2008;Odgers et al, 2005). However, some contradictory findings also exist (Hemphala, Kosson, Westerman, & Hodgins, 2015). By Table 3 Linear regression models of different type of recent (in the last 12 months) victimization predicting APSD-SR total scores in the total sample (n = 4855).…”
Section: Discussionmentioning
confidence: 99%